2013
DOI: 10.3390/nu5082969
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Dietary Antioxidant Status as Cardiovascular Disease Risk Factors: A Review of Human Studies

Abstract: Extensive evidence has demonstrated that many antioxidants such as vitamin C, vitamin E, carotenoids and polyphenols have protective effects in preventing cardiovascular disease (CVD), a chronic disease that is mediated by oxidative stress and inflammation. This review focuses on evidence from prospective cohort studies and clinical trials in regard to the associations between plasma/dietary antioxidants and cardiovascular events. Long-term, large-scale, population-based cohort studies have found that higher l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
122
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(127 citation statements)
references
References 176 publications
4
122
0
1
Order By: Relevance
“…GSH, albumin, SH-groups), and antioxidant enzymes (e.g. SOD, CAT, GPx) [Wang et al, 2013]. Unlike these parameters showing the level of protection, malondialdehyde (MDA) represents one of the lipid peroxidation products and is a marker of oxidative damage [Del Rio et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…GSH, albumin, SH-groups), and antioxidant enzymes (e.g. SOD, CAT, GPx) [Wang et al, 2013]. Unlike these parameters showing the level of protection, malondialdehyde (MDA) represents one of the lipid peroxidation products and is a marker of oxidative damage [Del Rio et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a direct correlation between a human diet rich in fruit, berries and vegetables containing high levels of carotenoids, and higher levels of serum carotenoids and lower risk of disease including several forms of cancer, cardiovascular and degenerative diseases (Virtamo et al, 2003;Wang et al, 2013;Fiedor and Burda, 2014). The ascribed health benefits of these natural foods cannot be unequivocally associated to the intake of carotenoids alone, since other antioxidant compounds present in the foods are ingested, such as vitamins, folate, and phenolic compounds (Virtamo et al, 2003;Voutilainen et al, 2006).…”
Section: Relevance Of Carotenoids To Human Healthmentioning
confidence: 99%
“…The ascribed health benefits of these natural foods cannot be unequivocally associated to the intake of carotenoids alone, since other antioxidant compounds present in the foods are ingested, such as vitamins, folate, and phenolic compounds (Virtamo et al, 2003;Voutilainen et al, 2006). Epidemiological evidence shows that people who ingest more dietary carotenoids exhibit a reduced risk for cancer, yet results from intervention trials indicate that the supplemental β-carotene does not prevent cardiovascular diseases or cancer (Chatterjee et al, 2012;Karppi et al, 2012;Wang et al, 2013), and may enhance lung cancer incidence and mortality among smokers (Omenn et al, 1996;Russell, 2002;Virtamo et al, 2003). The inefficient use of β-carotene as chemopreventive agent has been tentatively linked to cell-specific effects of the carotenoid in in vitro cultures: absence of effect on gap junctional intercellular communication (GJIC), Cx43 expression and growth of non-transformed or neoplastic murine lung epithelial cells, and enhanced GJIC, Cx43 expression and reduced growth of murine fibroblasts (Banoub et al, 1996).…”
Section: Relevance Of Carotenoids To Human Healthmentioning
confidence: 99%
“…Carotenoids are potent antioxidant molecules with 43 antioxidant properties and their dietary intake and plasma levels have been associated with a 44 decreased risk of chronic diseases, including type-2 diabetes (Akbaraly, Fontbonne, Favier, & 45 Berr, 2008), cardiovascular diseases (Y. Wang, Chun, & Song, 2013) and several types of 46 cancer (Tanaka, Shnimizu, & Moriwaki, 2012). Some exhibit provitamin A properties, 47 M A N U S C R I P T…”
Section: Introduction 27 28mentioning
confidence: 99%